PREVALENCE OF HEPATIC DYSFUNCTION IN PATIENTS WITH PLASMODIUM FALCIPARUM MALARIA IN A TERTIARY CARE HOSPITAL (The Research of Medical Science Review, 2025)
Objective: To determine the frequency of hepatic dysfunction in patients with plasmodium falciparum malaria visiting tertiary care hospital.Study design: Cross sectionalPlace & duration of study: Department of Medicine, Liaquat University of Medical & Health Sciences, Jamshoro.Methodology: In this cross-sectional observational study, a total of 196 patients of either gender having age between 18-70 years presented with plasmodium falciparum malaria with duration ≤ 2 weeks were included. The blood samples of all the patients was collected in a sterile manner for serum ALT, AST and bilirubin levels to assess the outcome variable i.e. hepatic dysfunction. Data analysis were done using SPSS Version 26. The quantitative variables were presented as mean ± SD. Frequencies & percentages were calculated for qualitative variables.Results: A total of 196 patients with plasmodium falciparum malaria were included in this study. The mean age of the patients was 36.14 + 11.1 years and mean duration of malaria was 1 + 0.5 weeks. Most of the patients were male 117 (59.7%) and 79 (40.3%) were female. 28 (14.3%) were hypertensive and 24 (12.2%) were diabetics. Out of 196 patients with plasmodium falciparum malaria, hepatic dysfunction found in 75 (38.3%).Conclusion: Our study concluded that frequency of hepatic dysfunction in falciparum malaria is very high, though it is commoner and more severe in the former.